Strategy For Strengthening Competitiveness Through Swot Analysis At CV. Anggita Dwi Pratama - Dimas Yoga Arif Pratama; Ida Ayu Made E.G; Kimas Kurniawan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the Marketing Strategy of furniture products from CV. Anggita Dwi Pratama, Kabupaten Seluma, using the SWOT analysis method, which includes four basic components: Strengths, Weaknesses, Opportunities, and Threats, with a sample of 14 respondents. The results of the study show that the results of the recapitulation of IFAS and EFAS scores obtained that the IFAS matrix shows the strengths of the factors and weaknesses of the quadrant - 0.171, then this shows that the business of CV. Anggita Dwi Pratama furniture products in Seluma Regency is in a weak internal position. While the EFAS matrix shows that the opportunity and threat factors show a quadrant of 0.232., then this shows that the business of CV. Anggita Dwi Pratama furniture products in Seluma Regency is in a fairly favorable situation, the company faces various external threats and internal weaknesses.